2021
DOI: 10.1029/2020wr028571
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Colloid Transport and Retention Using a Pore‐Network Model With Roughness and Chemical Heterogeneity on Pore Surfaces

Abstract: Colloid transport and retention in porous media is a common phenomenon in both nature and industry. However, many questions remain on how to obtain colloid transport and retention parameters. Previous work usually assumed constant transport parameters in a medium under a given physicochemical condition. In this study, pore‐network modeling is employed to upscale colloid transport and retention from the pore‐scale to the macro‐scale. The pore‐scale transport parameters including the collection efficiency (η), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Therefore, obtaining the collection efficiency η , as we did in this study, is a crucial step in quantifying colloid attachment also in the presence of repulsive barriers. Recent research on cylindrical pore throats (Lin et al., 2021, 2022) has shown that not only is η highly sensitive to fluid velocity, colloid size, and pore size, in agreement with our study, but so is the sticking efficiency for characterizing attachment through energy barriers. Since the fluid velocity and the ratio of colloid radius to pore radius changes drastically within a single constricted tube pore, and since pore shapes are heterogeneous in real soils, future research is necessary to elucidate the effects of pore throat geometry and orientation on the sticking efficiency.…”
Section: Implications For Continuum‐scale Colloid Transport Modelingsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, obtaining the collection efficiency η , as we did in this study, is a crucial step in quantifying colloid attachment also in the presence of repulsive barriers. Recent research on cylindrical pore throats (Lin et al., 2021, 2022) has shown that not only is η highly sensitive to fluid velocity, colloid size, and pore size, in agreement with our study, but so is the sticking efficiency for characterizing attachment through energy barriers. Since the fluid velocity and the ratio of colloid radius to pore radius changes drastically within a single constricted tube pore, and since pore shapes are heterogeneous in real soils, future research is necessary to elucidate the effects of pore throat geometry and orientation on the sticking efficiency.…”
Section: Implications For Continuum‐scale Colloid Transport Modelingsupporting
confidence: 92%
“…In such a case, nanoscale charge heterogeneity may also facilitate attachment under mean-field repulsive conditions, but is beyond the scope of this study, though we note that numerical models that consider this are available for other pore geometries (e.g., Johnson, 2020;Rasmuson, VanNess, et al, 2019). Possible attachment through energy barriers may be characterized by combining the collection efficiency with a sticking efficiency parameter (Lin et al, 2021(Lin et al, , 2022, which is at least in the first order independent of the collection efficiency. Thus, we only simulate purely attractive DLVO potentials, representing favorable attachment conditions, to obtain the collection efficiency (Molnar et al, 2015).…”
Section: Dlvo Interactionsmentioning
confidence: 99%
“…The formulations for 1D-averaged deposition rate coefficients at SWI, AWI, and AWS proposed in this study are applicable only for partially drained pores. For fully saturated pores, the deposition rate coefficients at SWI can be calculated using the formulations proposed by Seetha et al (2017), or by following the approach of Lin et al (2021Lin et al ( , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Some models have shown that the inhibition of colloid migration increases with solid surface roughness. 16,17 Most previous studies have focused on the migration of colloids in columns of glass beads or quartz sand that were employed as models for naturally occurring transport solids, and show that those columns do not normally hinder the migration of well-dispersed colloids. 11,12,18 Nonetheless, natural porous media are composed of distinct mineral constituents with surface characteristics that are much more complicated than those of quartz sand or glass beads, and those characteristics have different effects on colloid transport.…”
Section: Introductionmentioning
confidence: 99%